2020
DOI: 10.1186/s40798-020-00251-0
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol and Sports Performance: a Narrative Review of Relevant Evidence and Recommendations for Future Research

Abstract: Cannabidiol (CBD) is a non-intoxicating cannabinoid derived from Cannabis sativa. CBD initially drew scientific interest due to its anticonvulsant properties but increasing evidence of other therapeutic effects has attracted the attention of additional clinical and non-clinical populations, including athletes. Unlike the intoxicating cannabinoid, Δ 9-tetrahydrocannabinol (Δ 9-THC), CBD is no longer prohibited by the World Anti-Doping Agency and appears to be safe and well-tolerated in humans. It has also becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 201 publications
0
48
0
9
Order By: Relevance
“…One pharmaceutical CBD product (Epidiolex®) is currently approved in Europe for the therapy of a serious form of epilepsy in children (Dravet syndrome) 13 . However, CBD products are frequently sold as nutritional supplements, novel foods, or cosmetics and can be purchased in pharmacies, organic shops, drugstores, supermarkets, and via the Internet, and a growing receptivity amongst elite athletes is conceivable 14–16 …”
Section: Introductionmentioning
confidence: 99%
“…One pharmaceutical CBD product (Epidiolex®) is currently approved in Europe for the therapy of a serious form of epilepsy in children (Dravet syndrome) 13 . However, CBD products are frequently sold as nutritional supplements, novel foods, or cosmetics and can be purchased in pharmacies, organic shops, drugstores, supermarkets, and via the Internet, and a growing receptivity amongst elite athletes is conceivable 14–16 …”
Section: Introductionmentioning
confidence: 99%
“…CBD has been touted as a special case, widely perceived by non‐clinicians as relatively non‐toxic 5 . However, this is not consistent with clinical experience, particularly noting the potential for CBD‐related drug interactions 6 .…”
mentioning
confidence: 99%
“…Although being explicitly excluded from the Prohibited List by WADA, the natural cannabinoid receiving most attention lately in the context of sport and doping is cannabidiol (CBD). It has been considered as non‐intoxicating and potentially (or evidently) beneficial as anti‐inflammatory, analgesic, anxiolytic, and/or neuroprotective compound, and yet the global regulatory status is complex, ranging from classifying CBD as a controlled substance to allowing for CBD products being sold as nutraceuticals 171,172 . Further, the quality of several CBD products has been questioned, especially concerning the substantial presence of other natural cannabinoids (e.g., tetrahydrocannabinol, THC, cannabigerol, and cannabichromene), all of which could cause an AAF if detected at concentrations exceeding established thresholds or reporting levels 173 ; nevertheless, recent prevalence studies demonstrated that a considerable number of study participants from sports characterized by frequent high‐impact collisions have used CBD products for improved recovery, pain, and sleep management, largely without consulting a nutritionist 174 .…”
Section: Corticoids and Cannabinoidsmentioning
confidence: 99%
“…, and yet the global regulatory status is complex, ranging from classifying CBD as a controlled substance to allowing for CBD products being sold as nutraceuticals. 171,172 Further, the quality of several CBD products has been questioned, especially concerning the substantial presence of other natural cannabinoids prevalence studies demonstrated that a considerable number of study participants from sports characterized by frequent high-impact collisions have used CBD products for improved recovery, pain, and sleep management, largely without consulting a nutritionist. 174 In order to avoid inadvertent AAFs, thorough and immediate education of athletes and their entourage is recommended, also with regards to the use of products labeled as, for example, "light cannabis."…”
Section: β 2 -Agonistsmentioning
confidence: 99%